Case report: Low-dose radiation-induced meningioma with a short latency period - Li, Jinyang; Zhang, Xiangmao; Liu, Jing; Su, Chunxia; Cui, Junxiang; Yang, Liling; Gu, Yinghao (Frontiers in Oncology, 2024)
Patients with radiation-induced meningioma (RIM), most of whom had received head radiation therapy or had been exposed to ionizing radiation during childhood or adolescence, are at risk of developing cranial meningiomas throughout their lifetimes because of the long latency period. Although intermediate-to-high-dose ionizing radiation exposure is an established risk factor for RIM, risk factors for low-dose RIM remain incompletely defined. This study presents the case of a 56-year-old woman diagnosed with radiation-induced giant meningioma 2.5 years after undergoing an interventional embolization procedure for a brain aneurysm. This is the first report of RIM attributable to a brain intervention with an extremely short latency period. The total radiation dose received by the patient during the operation was 1367.3 mGy, representing a low dose. Our case report strengthens the evidence that even low radiation doses can increase the risk of RIM. These findings provide a realistic basis for the theoretical study of RIM and suggest some new ideas for RIM treatment. The need for caution in the use of radioactive treatments and optimization of interventional procedures is highlighted.